Uncovering the Disparities in Educational Attainment across Urban and Rural Locations in Northern Ireland - Cherry, Gemma (International Journal of Population Data Science, 2018)
Background Previous research investigating the influence of location in young people’s educational development often focus on measuring levels of poverty in urban communities and largely ignores the impact of rural areas and comparisons between urban and rural locations. This research advocates that including urban and rural location variables in research methodologies is imperative to gaining a fuller understanding of educational inequalities. Objectives The aim of this research is to examine the disparities in educational attainment between urban and rural locations in Northern Ireland (hereafter NI) and to identify the possible factors associated with such location disparities. Minimal research efforts have been dedicated to understanding these inequalities and even less attention has been aimed towards explaining them in a NI context. This research aims to fill this gap in knowledge. Methods A quantitative methodology, incorporating secondary data analysis will be utilised to achieve the research aims. This research will use administrative data provided by ADRC-NI which links the 2011 Census to the School Leavers Survey and School Census. Using GCSE results as a measure of educational attainment, multilevel modelling will be conducted on this data which has a sample size of N = 55,000 pupils. Findings The findings of this research will provide information on how much of the variance in pupils’ educational attainment across urban and rural locations is associated with the individual, the school and the location. Conclusions This research will add to the body of knowledge surrounding educational inequalities in NI.